Design of centrifugal compressors for heat pump systems. (15th December 2018) - Meroni, Andrea; Zühlsdorf, Benjamin; Elmegaard, Brian; Haglind, Fredrik
Highlights: A mean-line model for design and analysis of centrifugal compressors is presented. The model is validated against five test cases including three different fluids. The model is coupled to that of a high-temperature heat pump and optimized. The optimization method accounts for trade-offs in cycle and compressor designs. A two-stage steam compressor yields the best cycle performance. Abstract: This work presents a mean-line model of a centrifugal compressor and a method for a coupled optimization with a heat pump system. The compressor model was validated with five test cases from the open literature including the working fluids: air, refrigerant R-134a and carbon dioxide. Afterwards, the compressor model was coupled and optimized with that of a heat pump cycle supplying steam at 150 °C. Two cycle configurations were considered: an open-loop system using steam, and a closed-loop system with five other working fluid candidates. The compressor was designed using a multi-objective optimization algorithm, which seeks to maximize simultaneously the cycle coefficient of performance and the supplied heat flow rate. The method employed in this work considers the possible trade-offs regarding cycle and compressor design criteria, and can be used to identify cost-effective solutions for the next generation of heat pumps. The obtained results suggest that a two-stage compressor using steam yields the highest values of coefficient of performance and heat supply, and at the same time requires a more challenging compressor design.